(untitled) (Revista de Crítica Literaria Latinoamericana, 2012)
Much has been written on the emergence of new forms of artistic and film production in Argentina in the 2000s, in particular collective and/or innovative means of production in the "post-crisis". We propose a reading of poems by poet-activists —Arturo Carrera, Washington Cucurto, and Sergio Raimondi— in order to examine the coherence, or otherwise, between activism and poetics.